Harmoni Teologi Perjanjian Baru terhadap Keseimbangan Pemahaman dan Praktik dalam Jemaat Modern - Weriska Palopak; Inova Sri Bulawan; Desni Seliati Lapu’; Uci Ulpasila (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research explores the harmony between understanding New Testament theology and its application in the context of the modern congregation. Through a qualitative approach, we analyzed theological beliefs and daily practices in several congregations. Findings suggest that a good balance between understanding New Testament theology and its practical application forms a solid foundation for spiritual growth and transformation in the church community. Practical implications of this research include strategies for deeper religious education, spiritual formation, and the development of ministry initiatives that reflect the principles of New Testament theology. In conclusion, this harmony not only stimulates individual growth but also shapes the collective character of the congregation, strengthening the relevance of New Testament theology in facing the dynamics of the modern congregation.